Oral manifestations in AIDS patients receiving antiretroviral therapy in a referral hospital in Peru - Ramos Tejada, Katherine Liset; Romero Gamboa, Julio César; La Serna, Paola (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of oral manifestations in AIDSpatients, under antiretroviral therapy in a referral hospital in Perú.Materials and methods: A prospective, not experimental,cross – sectional and quantitative study. There was a populationconsisting of 380 and a sample of 191 patients who metthe selection criteria. The instrument was an adapted datacollection form that consist of two parts, in one the personaldata and in another the most frequent oral manifestations.Results: The prevalence of oral manifestations in AIDSpatients under antiretroviral therapy in 59.50% with oralcandidiasis being the most frequent with 35.5%, the prevalenceof oral manifestations is higher in male gender with a 67%and in the age range between 18-25 years old in a 57%.Conclusions: There is a high prevalence of oral manifestations inpatients with AIDS under antiretroviral therapy, the most frequentbeing oral candidiasis in males and in those under 25 years old.Key words: HIV-1; Antiretroviral; Viral load; T lymphocytes